2023
DOI: 10.1503/cmaj.220926
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a hospital frailty risk measure using Canadian clinical administrative data

Abstract: Background: Accessible measures specific to the Canadian context are needed to support health system planning for older adults living with frailty. We sought to develop and validate the Canadian Institute for Health Information (CIHI) Hospital Frailty Risk Measure (HFRM). Methods: Using CIHI administrative data, we conducted a retrospective cohort study involving patients aged 65 years and older who were discharged from Canadian hospitals from Apr. 1, 2018, to Mar. 31, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…These data can be readily integrated into clinical computer systems, automatically populated, and made available without requiring additional resource input [ 44 ]. Further, although we found some studies that used large sample sizes comprised of more than 200,000 participants [ 18 , 20 , 28 , 31 , 43 , 44 , 47 ], this did not necessarily mean that the predictors or outcome variables were distinctive. In addition, although many studies used administrative claims data, the use of billing information or the construction of cost predictors was rarely observed.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These data can be readily integrated into clinical computer systems, automatically populated, and made available without requiring additional resource input [ 44 ]. Further, although we found some studies that used large sample sizes comprised of more than 200,000 participants [ 18 , 20 , 28 , 31 , 43 , 44 , 47 ], this did not necessarily mean that the predictors or outcome variables were distinctive. In addition, although many studies used administrative claims data, the use of billing information or the construction of cost predictors was rarely observed.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, frailty was used in 8 studies. Among these 8 studies, 5 reported the development and validation of prediction models using different frailty index scores [ 27 , 28 , 33 , 35 , 44 ]. Another structured score that was used to predict NHA was the Identification of Seniors at Risk score, which is a standardized, comprehensive geriatric assessment tool administered at admission to a hospital [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Por ello, la Universidad de Dalhousie durante la pandemia por COVID-19 propuso elaborar un algoritmo enfocado en las comorbilidades, alteraciones de salud autorreportadas, dependencia para actividades básicas e instrumentales de la vida diaria que podrían ayudar a determinar el nivel de fragilidad en adultos mayores de manera más certera. El presente estudio tuvo como objetivo determinar la relación entre el algoritmo propuesto por la Universidad de Dalhousie y la Escala Clínica de Fragilidad (CFS) en adultos mayores en diferentes niveles asistenciales durante la pandemia por COVID-19 (1,2) .…”
Section: Sr Editorunclassified